Colpodella sp. (Phylum Apicomplexa) Identified in Horses Shed Light on Its Potential Transmission and Zoonotic Pathogenicity - Xu, Ming; Hu, Yang; Qiu, Hongyu; Wang, Jingyuan; Jiang, Jiafu (Frontiers in Microbiology, 2022)
Colpodella species, which mainly feed on protists and algae, are free-living close relatives of apicomplexans. Recent reports have identified Colpodella sp. infections in an immunocompromised individual and a suspected case of tick-transmitted infection resulting in neurological symptoms. Our molecular examination of piroplasmosis-infected horses in China identified nearly whole 18S rRNA gene sequences that are closely related to Colpodella sp. ATCC 50594 isolated from brown woodland soil at Gambrill State Park, located in Frederick, MD, shedding light on an underreported emerging zoonotic pathogen.